2017
DOI: 10.3389/fpls.2017.01915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Competition, Drought Stress and Photosynthetic Productivity on the Radial Growth of White Spruce in Western Canada

Abstract: Understanding the complex interactions of competition, climate warming-induced drought stress, and photosynthetic productivity on the radial growth of trees is central to linking climate change impacts on tree growth, stand structure and in general, forest productivity. Using a mixed modeling approach, a stand-level photosynthetic production model, climate, stand competition and tree-ring data from mixedwood stands in western Canada, we investigated the radial growth response of white spruce [Picea glauca (Moe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 74 publications
4
11
0
Order By: Relevance
“…This finding was consistent with Yu et al [19], which showed climate factors had limited capacity in explaining the variation in diameter growth, while stand factors were the main drivers to diameter growth. Similar results have been found in other research [14,56,57], for example, Jiang et al [14] found for both trembling aspen and white spruce that the climate factors showed less effects on tree growth than that of stand factors. Alam et al [56] found for white spruce that diameter growth of trees was primary constrained by competition with minor effects from climate factors.…”
Section: Variable Importance In Predicating Individual Tree Dbh Growthsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding was consistent with Yu et al [19], which showed climate factors had limited capacity in explaining the variation in diameter growth, while stand factors were the main drivers to diameter growth. Similar results have been found in other research [14,56,57], for example, Jiang et al [14] found for both trembling aspen and white spruce that the climate factors showed less effects on tree growth than that of stand factors. Alam et al [56] found for white spruce that diameter growth of trees was primary constrained by competition with minor effects from climate factors.…”
Section: Variable Importance In Predicating Individual Tree Dbh Growthsupporting
confidence: 90%
“…Similar results have been found in other research [14,56,57], for example, Jiang et al [14] found for both trembling aspen and white spruce that the climate factors showed less effects on tree growth than that of stand factors. Alam et al [56] found for white spruce that diameter growth of trees was primary constrained by competition with minor effects from climate factors. Besides, our results noted that the relative importance of site factors was less than that of stand factors and climate factors.…”
Section: Variable Importance In Predicating Individual Tree Dbh Growthsupporting
confidence: 90%
See 1 more Smart Citation
“…Some of the differences in tree-level climate sensitivity can be explained, and should not necessarily be treated as noise. Earlier studies have shown that parameters like competition, nitrogen deposition, and tree-height-related wood anatomical changes affect climate sensitivity [19][20][21]32,59,66]. In this study, we demonstrated how to visually detect potential causes of different climate sensitivities.…”
Section: Potential Further Analysesmentioning
confidence: 79%
“…This article addresses the principle of aggregated tree growth and the accumulating evidence that various parameters influence the climate sensitivity of individual trees, such as, competition [21,25,66], age [29,57], and height [56,59]. The methods described here highlight individual tree differences and potential causes.…”
Section: Discussionmentioning
confidence: 99%